Global Entrepreneurship : Environment and Strategy - Kshetri, Nir; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
This second edition of a Choice Outstanding Academic Title improves coverage of the global environments in which entrepreneurs operate. In Global Entrepreneurship: Environment and Strategy, Nir Kshetri explores and illuminates the economic, political, cultural, geographical, and technological environments that affect entrepreneurs as they exploit opportunities and create value in economies around the world.Grounded in theory, the book begins by laying out the concepts, indicators, and measurements that have unique impacts on entrepreneurs in different regions. This framework sets the scene for a close examination of global variations in entrepreneurial ecosystems and finance. Kshetri methodically examines entrepreneurship patterns in diverse economies through the lenses of economic system, political system, culture and religion, and geography (both by country and continent) - and for the first time, includes an entire chapter on entrepreneurship in Latin America.All new for this edition, Global Entrepreneurship offers case studies at the end of each chapter to illustrate relevant concepts, as well as two detailed cases in an appendix, to encourage broader reflection. The book is accompanied by online resources, bringing additional value for instructors and students in entrepreneurship and international business classes.
Chapter 1. Global Entrepreneurship: The Current Status, Definitions, Types and Measures Chapter 2. The Entrepreneurial Ecosystem and Its Components Chapter 3. Sources of Entrepreneurial Finances and Their Variation across the World Chapter 4. Entrepreneurship in OECD Economies Chapter 5. Entrepreneurship in Post-Socialist Economies in Former Soviet Union and Central and Eastern Europe Chapter 6. Entrepreneurship in the Gulf Cooperation Council Economies Chapter 7. Entrepreneurship in Africa Chapter 8. Entrepreneurship in China Chapter 9. Entrepreneurship in India Chapter 10. Entrepreneurship in Latin America
Includes bibliographical references and index.
Also available in print format.
Keywords: Entrepreneurship -- Developing countries; Entrepreneurship